2004
DOI: 10.1097/00054725-200409000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Gastric Acid and Pancreatic Enzyme Secretion in Patients With Crohn’s Disease May be a Consequenece of a Poor Nutritional State

Abstract: Malnutrition may play a significant role in the impairment of gastric acid and pancreatic secretion in Crohn's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…It was found that GI energy excretion was higher in an underweight group with CD than in a normal weight group, despite no differences between the two groups for dietary energy intake or resting metabolic rate. Similarly, in another study, malabsorption and increased faecal fat were observed in severely undernourished patients, which was attributed to the impaired gastric acid and pancreatic enzyme secretion in patients with CD (Winter et al, 2004). Interestingly, gastric acid and pancreatic enzyme secretion were severely impaired in 80% of these patients (Winter et al, 2004).…”
Section: Increased Gi Nutrient Lossesmentioning
confidence: 75%
See 1 more Smart Citation
“…It was found that GI energy excretion was higher in an underweight group with CD than in a normal weight group, despite no differences between the two groups for dietary energy intake or resting metabolic rate. Similarly, in another study, malabsorption and increased faecal fat were observed in severely undernourished patients, which was attributed to the impaired gastric acid and pancreatic enzyme secretion in patients with CD (Winter et al, 2004). Interestingly, gastric acid and pancreatic enzyme secretion were severely impaired in 80% of these patients (Winter et al, 2004).…”
Section: Increased Gi Nutrient Lossesmentioning
confidence: 75%
“…, 2004). Interestingly, gastric acid and pancreatic enzyme secretion were severely impaired in 80% of these patients (Winter et al. , 2004).…”
Section: Increased Gi Nutrient Lossesmentioning
confidence: 99%
“…Amino acid (L-[1-14 C]leucine) isotope incorporation studies were performed to study pancreatic enzyme protein kinetics in undernourished patients with Crohn's disease[75]. Results revealed impairment of synthesis of the enzymes amylase and trypsin, with marked decrease in zymogen pool size (amylase 1516 AE 874.9 versus 6838 AE 1039 U, P < 0.01; trypsin 417.0 AE 178.3 versus 932.4 AE 142.3 U, P < 0.05), suggesting pancreatic atrophy.…”
mentioning
confidence: 99%
“…First is malnutrition with incidence of 25-80% [12]. Malnutrition may diminish gastric acid secretion [13], which represents a barrier for infection [14]. Another barrier for Salmonella infection is normal intestinal fl ora [14], which was probably disrupted in our patient because of long-lasting CD.…”
Section: Discussionmentioning
confidence: 99%